망막분지정맥폐쇄에서 패턴 광응고술과 기존의 광응고술과의 효과 비교 - 박영근; Young Gun Park; 지동현; Dong Hyun Jee; 양지욱; Ji Wook Yang (Daihan angwa haghoi jabji, 2010)
목적: 망막분지정맥폐쇄로 인하여 신생혈관이 발생한 환자에서 패턴 광응고술과 기존의 광응고술과의 치료 효과 및 합병증 여부를 비교하고자 하였다. 대상과 방법: 환자 36명(39안)을 대상으로 패턴 광응고술 시행군은 0.02초의 레이저 노출 시간을 이용하여 패턴 방식(3×3)을 사용하였고, 기존 광응고술 시행군은 0.2초의 노출 시간을 이용하였으며 그 외 광응고반의 크기 및 강도는 동일하게 시행하였다. 시술 전 및 시술 후 2, 4, 8, 12주에 최대교정시력 및 중심황반두께를 측정하였으며, 시술 직후 환자의 통증 정도를 비교하였다. 6개월 이상 경과 관찰 기간 동안 신생혈관 퇴행 여부를 조사하였다. 결과: 환자가 느끼는 통증의 정도는 패턴 광응고술 시행군에서 유의하게 적었다. 술 후 최대교정시력의 변화는 두 군 간 차이가 없었으며, 중심황반두께의 증가는 패턴 광응고술 시행군에서 적었으나 시술 후 8, 12주에 통계적으로 유의하였다. 신생혈관 퇴행 비율은 두군 간 차이가 없었다. 결론: 짧은 레이저 노출 시간을 이용한 광응고술은 기존과 비교하여 치료 효과에 차이가 없었으며, 환자의 통증이 적고, 초기 황반부종 등 합병증이 적은 효과적인 방법으로 생각된다. <대한안과학회지 2010;51(10):1368-1373> Purpose: To compare the clinical effect and complications between patterned laser photocoagulation with short exposure time and conventional laser photocoagulation for neovascularization in branch retinal vein occlusion (BRVO). Methods: A prospective study was conducted on 36 patients (39 eyes) who required laser photocoagulation for neovascularization due to BRVO. The patients were divided into 2 groups, the patterned laser photocoagulation group (laser exposure time 0.02 sec, 3 × 3 array patterned photocoagulation) and conventional laser photocoagulation group (laser exposure time 0.2 sec). Other laser parameters (burn intensity and spot size) were the same. Pain score at the time of treatment was monitored after the laser photocoagulation. In addition, best-corrected visual acuity as well as central macular thickness measurements were performed before the treatment and after 2, 4, 8, and 12 weeks. The regression of neovascularization in fluorescein angiography was monitored during follow-up periods. Results: The patterned laser photocoagulation group had a greater reduction in pain during laser photocoagulation, and a decreased change in central macular thickness after laser photocoagulation than the conventional laser photocoagulation group. In particular, the patterned laser photocoagulation group had a statistically significant difference between the 2 groups at postoperative 8 and 12 weeks. The regression rate of neovascularization between the 2 groups had no statistically significant difference. Conclusions: Patterned laser photocoagulation with a short exposure time decreases pain and postoperative macular edema with no difference in regression of neovascularization. Patterned laser photocoagulation with a short exposure time can be considered as a useful and efficient method for neovascularization in BRVO. J Korean Ophthalmol Soc 2010;51(10):1368-1373